2022
DOI: 10.1371/journal.pone.0262780
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices of lifestyle modification and associated factors among hypertensive patients on-treatment follow up at Yekatit 12 General Hospital in the largest city of East Africa: A prospective cross-sectional study

Abstract: Background Hypertension is a devastating global public health challenge; studies indicated that Ethiopia has been affected by the burden of hypertension especially in urban areas. The overall prevalence of hypertension in Ethiopia was estimated to be 19.6% (23.5% in urban and 14.7% in rural population). Along with medical management of hypertension, appropriate lifestyle modification is a crucial and inexpensive means of hypertension control. The main purpose of the study was therefore to assess knowledge, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 46 publications
2
17
1
Order By: Relevance
“…There is a high probability of increased interaction of the respondents with students of the tertiary institutions, thereby increasing their knowledge of the subject matter. The findings are in line with the study by Kebede, Taddese, Girma (2022), andPapathanasiou, et al (2020) who in their different studies reported no significant difference in knowledge of physical activity on blood pressure distribution by class of the students.…”
Section: Knowledge By Class Of the Students And Physical Activity On ...supporting
confidence: 92%
See 2 more Smart Citations
“…There is a high probability of increased interaction of the respondents with students of the tertiary institutions, thereby increasing their knowledge of the subject matter. The findings are in line with the study by Kebede, Taddese, Girma (2022), andPapathanasiou, et al (2020) who in their different studies reported no significant difference in knowledge of physical activity on blood pressure distribution by class of the students.…”
Section: Knowledge By Class Of the Students And Physical Activity On ...supporting
confidence: 92%
“…The findings from the present study showed a high level of good knowledge of the effect of physical activity on blood pressure among respondents. The findings were in agreement with the study of Kebede and Taddese, Girma (2022) who reported that almost half of the study participants had a favourable knowledge regarding blood pressure distribution among adolescents, but it is only around one-third of the participants had good practices. The current study findings also agree with the study conducted in Nigeria which reported 60% knowledge of blood pressure distribution among adolescents (Osuala, Oluwatosin, Kadiri 2014).…”
Section: Good Knowledge Of Physical Activity On Blood Pressure Among ...supporting
confidence: 91%
See 1 more Smart Citation
“…Although the prevalence of hypertension is higher in economically developed countries than in economically developing countries (37% and 23%, respectively, in adults), about two‐thirds of the total affected population currently lives in developing regions 33 . Overall, low‐ and middle‐income nations account for more than 80% of the disease burden associated with hypertension 26,34 . In high‐income countries, older age groups (60 years and older) bore most of the burden compared to low‐ and middle‐income countries, middle‐age groups (40–59 years) 35 .…”
Section: Monitoring and Management Of Hypertension In Primary Health ...mentioning
confidence: 99%
“…Obesity increases the risk of non-communicable diseases like hypertension and diabetes as well as worsens the prognosis of these diseases where they are present (Akinkugbe, 1997;Ojeogwu & Husin, 2020). Noncommunicable diseases cause significant morbidity and mortality worldwide, with low-and middle-income countries (LMIC) like Nigeria bearing the brunt of the burden (Kebede, 2022). About 25% of the global population and 15% of Africans currently have hypertension which is set to increase if not checked (Angelo 2020).…”
Section: Introductionmentioning
confidence: 99%